0433 Quality Of Life And Depressive Symptoms In Midlife Women With And Without Insomnia. (27th April 2018) - Claudatos, S A; Sassoon, S A; de Zambotti, M; Goldstone, A; Colrain, I M; Baker, F C
Abstract: Introduction: Insomnia affects upwards of 40% of midlife women. Insomnia disorder, as well as associated symptoms like depression, may produce significant impairment in daily functioning. In this study, we compared quality of life and impact of menopausal symptoms on quality of life domains between women, all in the menopausal transition, with (n=54) and without (n=46) insomnia disorder. We also investigated the association of depressive symptoms with quality of life within each group. Methods: One hundred women (49.3 ± 3.25 years) underwent a clinical structured interview including a sleep history module to establish the presence of insomnia disorder. Women also completed clinical measures assessing depressive symptoms (Beck Depression Inventory-II, BDI), quality of life, and impairment associated with menopausal symptoms (Menopause-Specific Quality of Life, and Work and Social Adjustment Scale). Results: Women with insomnia compared with good sleepers had a poorer quality of life (p = 0.002) and greater impairment associated with vasomotor (hot flashes), psychological, and physical symptoms (p<0.05). They also reported more impairment in work, social leisure activities, and functioning in relationships, attributed to their menopausal symptoms, compared to controls (p<0.001). BDI scores were higher in the insomnia (7.52 ± 5.43, median=7) than control (3.48 ± 3.77, median=2) group, although none of the women met DSM-IV criteria for mood disorders. Within the insomnia (r= -0.48, p<0.01) and control (r = -0.48, p<0.01) groups, higher BDI scores were associated with a poorer quality of life. Conclusion: Menopausal women with insomnia disorder have a poorer quality of life and more impairment across several domains. Over and above the impact of insomnia, symptoms of depression are associated with poorer quality of life enjoyment and satisfaction in midlife women. It is critical to recognize and treat menopausal insomnia and depressive symptoms to improve overall quality of life. Support (If Any): This study was supported by the HL088088 grant (FCB).